Los caminos Wari entre Moquegua y Majes en el sur del Perú - Williams, Patrick Ryan (Pontificia Universidad Católica del Perú, 2023)
From its capital in the Ayacucho highlands of Peru, the Wari Empire spread its influence over 1300 lateral kilometers from Cajamarca in the north to Cuzco and Moquegua in the south. Along its southern periphery, Wari presence has been documented most convincingly between 1000 and 3000 meters in elevation in valleys such as the Ocoña, Majes, Sihuas, Vitor, Chili, and Moquegua, where archaeological survey has been carried out in parts of this 300-kilometer stretch of the southern Peruvian sierra. In this paper, I examine the evidence for a Wari southern road and the settlements that connected the far southern part of Peru and eventually to the Ayacucho heartland to the north. I argue that the quichua ecological niche is a primary focus of Wari cultural landscapes and dictated the placement of the principal Wari road network. I further examine the organization of settlement along the proposed royal road, as well as the symbolic and demographic components of its route. Finally, I investigate the role of the Wari road in promulgating a Wari imperial political economy in the far south.

Con su capital en la sierra de Ayacucho, Perú, el Imperio Wari extendió su influencia por más de 1300 kilómetros, desde Cajamarca en el norte hasta Cuzco y Moquegua en el sur. A lo largo de su periferia sur, la presencia Wari ha sido mejor documentada entre los 1000 y 3000 metros sobre el nivel del mar en valles como Ocoña, Majes, Sihuas, Vitor, Chili y Moquegua, la mayoría de ellos prospectados arqueológicamente. En este artículo, examino las evidencias de un camino Wari sureño y un conjunto de sitios arqueológicos que conectaron el extremo sur del Perú con regiones más septentrionales y, eventualmente, con la capital ayacuchana. Argumento que el nicho ecológico quichua fue el foco principal de los paisajes culturales Wari y dictaminó la ubicación de la red vial principal de esta tradición. Asimismo, examino la organización de los asentamientos localizados a lo largo del camino real propuesto, así como los componentes simbólicos y demográficos de la ruta. Por último, investigo el rol del camino Wari en la promulgación de una economía política imperial en el extremo sur del Perú.
Wari roads in southern Peru from Moquegua to Majes
Keywords: Landscape archaeology; GIS; Exchange; Phenomenology; Cultural ecology; Arqueología del paisaje; SIG; Intercambio; Fenomenología; Ecología cultural; https://purl.org/pe-repo/ocde/ford#6.01.02